Provisão para sinistros : estudo de uma companhia de seguros espanhola - Castro, Francisca da Câmara Machado Rodrigues de (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management